2013
DOI: 10.1186/cc12839
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and protective role of autophagy in a mouse cecal ligation and puncture-induced sepsis

Abstract: IntroductionIt is not well understood whether the process of autophagy is accelerated or blocked in sepsis, and whether it is beneficial or harmful to the immune defense mechanism over a time course during sepsis. Our aim was to determine both the kinetics and the role of autophagy in sepsis.MethodsWe examined autophagosome and autolysosome formation in a cecal ligation and puncture (CLP) mouse model of sepsis (in C57BL/6N mice and GFP-LC3 transgenic mice), using western blotting, immunofluorescence, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 48 publications
5
94
1
Order By: Relevance
“…51 Conversely, administration of chloroquine abolishes autophagic flux, which results in the elevation of serum transaminase levels. 14 Compelling evidence confirms that autophagy in the liver is induced during the initial 4 h after CLP but declines after this point until 24 h. 11,14,19,36,51 The blockade of autophagic flux is demonstrated by reduced LAMP1 expression, accumulation of SQSTM1 and lack of colocalization of autophagosomes with lysosomes.…”
Section: Livermentioning
confidence: 74%
See 3 more Smart Citations
“…51 Conversely, administration of chloroquine abolishes autophagic flux, which results in the elevation of serum transaminase levels. 14 Compelling evidence confirms that autophagy in the liver is induced during the initial 4 h after CLP but declines after this point until 24 h. 11,14,19,36,51 The blockade of autophagic flux is demonstrated by reduced LAMP1 expression, accumulation of SQSTM1 and lack of colocalization of autophagosomes with lysosomes.…”
Section: Livermentioning
confidence: 74%
“…During the initial 4 to 6 h after CLP, hepatocytes and cardiomyocytes show a considerably higher LC3-II:LC3-I ratio (a marker of autophagy induction), accompanied by an increased number of autophagosomes. 11,14 However, the autolysosomal (the product of an autophagosome fusing with a lysosome) numbers decrease from 8 h onwards, leading to accumulation of SQSTM1/p62 receptor proteins. Survival of mice is increased by administration of carbamazepine, an autophagic flux modulator, as evidenced by an increase in LC3-II, RAB7 and a decreased level of the receptor protein SQSTM1.…”
Section: Kinetics Of Autophagy In Sepsismentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is activated in sepsis and exerts a protective role, by maintaining cellular homeostasis and limiting cell damage and death (20,21). Previous studies have demonstrated that autophagy protects against sepsis-induced apoptotic cell death in the liver (22,23) and kidney (24,25), as well as lung injury (26,27) and immune systems (9,10).…”
Section: Clinical Application: Restoration Of Immune Homeostasis By Amentioning
confidence: 99%